PENGENALAN CLOUD COMPUTING SEBAGAI PENUNJANG PEMBELAJARAN PADA PESANTREN NAFIDATUNNAJAH - Chandra Alim; Ahmad Fauzi; Herwis Gultom (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
The need for affordable, flexible, and efficient information technology is increasingly pressing in this rapidly evolving digital era. Cloud computing is one innovation that addresses this challenge. With this technology, users can use the internet to manage, store, and access data and applications without the need for local hardware. The activity, themed "Introducing Cloud Computing as a Learning Support (Definition, Benefits, Examples, and Implementation)," was conducted. Cloud computing allows students to save their work without worrying about data loss, access learning resources anytime and anywhere, and even interact with peers confidently. With cloud computing, data can be stored and programs can be run over the internet, eliminating the need to store everything on a computer or flash drive. Despite this, many students remain unsure about what cloud computing is, how it works, and why it is so important for the future of education and the world of work. Therefore, it is crucial for students to be better prepared for the ever-evolving digital world, improve their digital literacy, and acquire relevant and practical knowledge through appropriate outreach on cloud computing. Keywords: Cloud computing, cloud computing learning, Community Service.